The use of multimedia tools in the educational process (MMIT Proceedings, 2025)
This article explores the role and significance of multimedia tools in the modern educational process. It examines the types of multimedia technologies, their pedagogical potential, and their impact on students’ motivation and cognitive activity. Special attention is given to the didactic functions of multimedia, examples of their integration into school and higher education, as well as current challenges and future perspectives. The findings highlight that effective and pedagogically grounded use of multimedia enhances the quality of learning and contributes to the development of key 21st-century competencies